The phenomenon of quotation in textual studies - Ashirmatova Madina Zafarovna (Zien Journals, 2023)
This article provides information about the science of textual studies, citation as a phenomenon, and information about the phenomenon of citation in textual studies.
Keywords: textual studies; quotation; source; text